2007
DOI: 10.1136/oem.2006.031039
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine noise, annoyance and self-reported health and well-being in different living environments

Abstract: Objectives: To evaluate the prevalence of perception and annoyance due to wind turbine noise among people living near the turbines, and to study relations between noise and perception/annoyance, with focus on differences between living environments. Methods: A cross-sectional study was carried out in seven areas in Sweden across dissimilar terrain and different degrees of urbanisation. A postal questionnaire regarding living conditions including response to wind turbine noise was completed by 754 subjects. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
187
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(207 citation statements)
references
References 20 publications
10
187
4
2
Order By: Relevance
“…opinion about wind turbines in general and/or their visual impact on landscape, and self-reported sensitivity to noise increased the probability of being annoyed by the wind turbine noise [2,3], while obtaining economic benefits from wind turbines reduced the risk of annoyance [4]. It was also found that terrain and urbanization had impact on the perceived annoyance from the wind turbine noise [3].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…opinion about wind turbines in general and/or their visual impact on landscape, and self-reported sensitivity to noise increased the probability of being annoyed by the wind turbine noise [2,3], while obtaining economic benefits from wind turbines reduced the risk of annoyance [4]. It was also found that terrain and urbanization had impact on the perceived annoyance from the wind turbine noise [3].…”
Section: Introductionmentioning
confidence: 78%
“…It was also found that terrain and urbanization had impact on the perceived annoyance from the wind turbine noise [3]. In comparison to other European countries, especially the ones where the use of renewable energy sources is advanced, such as Germany, Spain or Denmark, Poland is just at the beginning of its "wind adventure".…”
Section: Introductionmentioning
confidence: 99%
“…For example, amplitude modulation, which may be experienced as audible pulsing, has been shown to increase annoyance among individuals proximate to rail yards (Kanteralis and Walker 1988). However, annoyance from wind turbine sound has also been found to be correlated with unrelated factors including prior attitude toward wind turbines, the visibility of the turbines, and whether or not individuals receive direct financial payments from a project (Pedersen and Waye 2007;Pedersen et al 2009). …”
Section: Barriersmentioning
confidence: 99%
“…12 Subjective and personal issues are bound to be involved; for example, people living in rural areas may well have moved there for the peace and quiet, and hence a negative reaction to wind turbines is unsurprising. 19 Indeed, some have suggested that personal and social factors can be so variable that it may not be feasible to develop a national noise policy. 12 …”
mentioning
confidence: 99%
“…14,18 Other interesting factors noted to be significant are visibility of the turbine and whether or not the responder benefits economically from the wind turbine. 18,19 It is also known that high levels of low frequency noise induce body vibrations, most prominently chest resonance vibration in the range of 50-80 Hz. 13 The lower a sound's frequency the longer its wavelength, which means resonance may occur in an enclosed or partially open space such as a room in a house, as well as within the body.…”
mentioning
confidence: 99%